2021
DOI: 10.1002/adfm.202104620
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Supporting Electrodes for Gas‐Involved Key Energy Reactions

Abstract: Self‐supporting materials are widely adopted in gas‐involved electrocatalysis during the past few decades because of their unique physical/electrochemical properties, especially the stabilized spatial framework and the large electrochemical interfaces. Reportedly, there is no clear definition to define “self‐supporting” materials, and also, no such comprehensive reviews have fully discussed the self‐supporting materials in gas‐involved electrochemical applications. Therefore, it is necessary to provide timely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 398 publications
0
26
0
Order By: Relevance
“…For OER, the potential corresponding to current density of 10 mA cm −2 (E j10 ) is 1.48 V, compared with 1.56 V for commercial RuO 2 catalysts. As shown in Figures 4B,E , Pd-Co 3 O 4 @CNF exhibits the lowest Tafel slopes (73.1 mV dec −1 and 65.7 mV dec −1 ) for both OER and ORR, revealing the enhanced reaction kinetics ( Wang et al, 2021 ). The Nyquist plots of catalysts as shown in Figures 3C,F demonstrated that Pd-Co 3 O 4 @CNF oxygen electrode has the lowest charge transfer resistance, indicating that the electrocatalysis process is enhanced .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…For OER, the potential corresponding to current density of 10 mA cm −2 (E j10 ) is 1.48 V, compared with 1.56 V for commercial RuO 2 catalysts. As shown in Figures 4B,E , Pd-Co 3 O 4 @CNF exhibits the lowest Tafel slopes (73.1 mV dec −1 and 65.7 mV dec −1 ) for both OER and ORR, revealing the enhanced reaction kinetics ( Wang et al, 2021 ). The Nyquist plots of catalysts as shown in Figures 3C,F demonstrated that Pd-Co 3 O 4 @CNF oxygen electrode has the lowest charge transfer resistance, indicating that the electrocatalysis process is enhanced .…”
Section: Resultsmentioning
confidence: 94%
“…Due to the close lattice structure, Pd is considered to have comparable performance with Pt in electrochemical applications ( Cheng et al, 2020 ). Riley synthesized dodecagon N-doped PdCoNi carbon-based nanosheets demonstrating superior performance for electrocatalytic water splitting and suitable for wide pH electrolytes ( Wang et al, 2021 ). Thus, combining Pd with composite substrates could significantly improve the proton transfer rate, reaction kinetics, thereby effectively enhancing the catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, significant research effort has been dedicated to the fabrication of different dimensional electrocatalysts with controlled 1D, 2D, and 3D morphologies with regulated size and shape on a variety of conductive substrates, such as tions, the catalysts need to provide continuous gas evolution (i.e., H 2 , O 2 ) at a high current density (≈1 A cm -2 with stability for a few thousands of hours), and the use of these powdery nanocatalysts coated on the current collector (typically glassy carbon; GC) is limited by the complex fabrication process and deterioration in electrocatalytic performance and stability. [55,64,75,76] Meanwhile, an inappropriate optimization/use of binders may lead to an increase of resistance, inhibit mass and charge transport and bury the real active sites, as shown in Figure 1a, to reduce the overall catalytic activity. In addition, the low electrical conductivity of several powder-based nanocatalysts necessitates the use of conductive additives (e.g., carbon black).…”
Section: Dimensionality Of Nano-and Microstructured Catalystsmentioning
confidence: 99%
“…The three-phase main steps during the electrode reaction are shown in Figures 1b and 2; these include i) mass transfer (i.e., transfer of ions/molecules from the bulk electrolyte to the electrocatalytic surface), ii) electron transfer from the substrate to electrocatalysts surface and iii) electrocatalytic surface reaction employing adsorption of ions/molecules, charge transfer, reconstruction of molecules, rupture/creation of chemical bonds, and desorption of reaction intermediates/products at the active sites surface. [76,[82][83][84] For an easier understanding, the effect of powder-based nanocatalysts and nano-and microstructured binder-free electrocatalysts on electrocatalytic activity is compared and discussed from two main perspectives such as electron transfer and mass transfer (Figure 2). As shown in Figures 1 and 2, engineering the dimensionality of nano-and microstructured catalysts on a conductive substrate has been widely employed as an effective strategy to improve catalytic performance.…”
Section: Dimensionality Of Nano-and Microstructured Catalystsmentioning
confidence: 99%
“…[31][32][33] With regards to the micro-structure influencing the electrocatalytic activity, the design and construction of self-supporting electrodes based on two-dimensional (2D) nanosheets are appealing in optimizing the mass transfer and utility rate of the active sites. [34][35][36][37][38][39] However, it is still challenging to tune the specific parameters of 2D nanosheet-based self-supporting multiple metal sulfide electrodes.…”
Section: Introductionmentioning
confidence: 99%